DAMPAK KEGIATAN OFF ROAD MOTOR TRAILTERHADAP KOMPOSISI DAN STRUKTUR JENIS TUMBUHAN BAWAH (STUDI KASUS HUTAN PINUS JAYAGIRI, LEMBANG) - Indri Wulandari; Teguh Husodo; Erri N. Megantara (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2017)
Activities off-road dirt bike into activities that provide satisfaction and pleasure for the perpetrators, but these activities have an impact on the presence of a groundcover vegetation cover the forest floor.The purpose of this study was to determine the composition and structure of the undergrowth around the track off-road dirt bike as the impact of off-road activities of undergrowth.The method used in this research is quantitative method. The data collection techniques using the method of squares size 1x1 meter placed on the track lane area, the edge of the lane path and the area that is not interrupted by off-road trail activities.Data analysis was performed by calculating to determine the dominant plant species under indicated by the value of the SDR.Based on research that has been done, there were 26 species of plants were found at the bottom of the sampling.The dominant plant species below shows that these types are resistant to the activity of the off-road trail.The dominant species groundcoverfound are Eupatorium riparium regal. Meanwhile, species groundcoverthat can survive with the activities of off-road trail, such as Cynodon dactylon, Eupatorium riparium, Alternanthera sp. and Eupatorium colonum. Key Word : Off-road, Species Groundcover, Structure Groundcover